Rhinogenic contact point headache mimicking odontogenic pain: A case report and review of literature - Abhishek G Soni (Wolters Kluwer Medknow Publications, 2020)
Headache is a common clinical problem, and appropriate diagnosis and management are a challenge for oral physician. Any minor anatomical variation within the nasal cavity may lead to mucosal contact point, which may be an etiological factor for causing headache and often left behind by clinician during preliminary evaluation of patients with headache or facial pain, resulting in misdiagnosis and inappropriate treatment. This article is an attempt to present a case of rhinogenic contact point headache which may be mistaken for a toothache initially leading to incorrect diagnosis and irrelevant treatment. A thorough, accurate and comprehensive history taking and a complete clinical and general physical examination result in appropriate diagnosis of the clinical situation.